Sistema de ecuaciones lineales: resolución de problemas con el uso del software GeoGebra - Figueroa Vera, Rocío (2018)
This report is part of a broader investigation and its purpose is to reflect on the resolution of linear equation system problems with two variables with the mediation of GeoGebra; in addition, the discovery of the handling of the variation of parameters, considered in both equations, as well as the implicit affine function, fixed parameters and variable parameters (variation of a coefficient and variation of an independent term). Aspects of the Theory of Didactic Situations have been considered and, for the design and implementation, the a priori and a posteriori analysis of Didactic Engineering have been considered, as well as the elements of the Theory of Semiotic Representation Registers. One of the results obtained refers to the fact that by means of an adequate use of GeoGebra it will be possible to recognize the effectof modifying one of the parameters whenstudying the behavior of the r.